PEMANFAATAN TUMBUHAN LAKUM (Cayratia trifolia (L.) Domin.) OLEH ETNIS MELAYU DI KECAMATAN SUNGAI KUNYIT KABUPATEN MEMPAWAH - Mukarlina, Budi Prasetyo, Riza Linda, (Universitas Tanjungpura, 2016)
Lakum (Cayratia trifolia ) is a wild plant which is classified into the Family Vitaceae. The use of lakum (C. trifolia) by ethnic Malays in Sungai Kunyit, Mempawah Regency has not been documented. This research aims to find out parts of the plant used, form and way of using lakum (C. trifolia) by ethnic Malays in Sungai Kunyit Subidstrict. The research was conducted in Sungai Kunyit for seven months from May to November 2015. Data were collected using interviews. The respondents or informants were determined using a purposive sampling technique. The total number of respondents was 33. There are three parts of lakum (C. trifolia) commonly used by Ethnic Malays, i.e. leaf (PPV = 0.185), stem (PPV = 0.032), and fruit (PPV = 0.782). Ethnic Malays often use the leaves as medicinal herb for swelling, ulcer and headache (IUV = 0.304), and the fruit is often used as seasoning (IUV = 0.52). the stems are only used as ropes (IUV = 1). The ways ethnic Malays in Sungai Kunyit use lakum (C. trifolia) are by boiling and mashing it. It is also used without processing.